The pronunciation of identical consecutive letters in the Yemenite Jewish tradition - Zur, Uri (HTS teologiese studies, 2020)
This article examines the pronunciation of identical consecutive letters in the Yemenite Jewish tradition, with a basic comparison with the pronunciation of identical letters in other present-day traditions. It is notable that in the Yemenite tradition also there are differences of opinion as to the pronunciation of these letters as a result of the effect of their pronunciation in other present-day traditions. In this article, we present the fundamental views with regard to the pronunciation of identical consecutive letters as well as their possible pronunciations in light of the grammar rules evident from the grammarians. The article does not purport to provide a historical, developmental or chronological investigation of the grammar rules; rather, it focuses on one specific topic involving the pronunciation of identical consecutive letters in the Yemenite tradition.